Socio-Economic Significance Of Organizing Marketing Activities In Sports - Bakhodir Muratovich Ishankulov (Euro Asian Journal Publishing, 2024)
Marketing in sports is a way to achieve high results in the production and service sectors using marketing strategies in the sports sector.
Keywords: Sports marketing; marketing strategy; strategic planning